Scrotal Pathology - Bertolotto, Michele; Trombetta, Carlo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Scrotal Pathology is a comprehensive practical guide to the management of patients who present with scrotal disorders. Introductory chapters consider imaging instrumentation, clinical evaluation, and clinical and imaging anatomy. The full range of disorders is then discussed in individual chapters organized according to clinical presentation. All clinical and imaging aspects are covered in depth, with full description of symptoms and explanation of the value of different clinical tests and imaging modalities. In addition, underlying histopathological features are presented and correlated with imaging features in order to clarify their pathological basis. For each disorder, therapeutic strategies are discussed and appraised. Adults and children are considered separately whenever necessary, bearing in mind that they often present essentially different scrotal pathology. The many images are all of high quality and were obtained using high-end equipment. The integrated information provided in this book will be invaluable in enabling different specialists to understand other perspectives and requirements and in filling gaps in knowledge.
Instrumentation, Technical Requirements 1.US -- 2.MRI -- Anatomy of the Scrotum -- Clinical Evaluation of Scrotal Disease -- Sonographic Scrotal Anatomy -- Scrotal Anatomy at MRI -- Scrotal Trauma: Mechanisms, Presentation and Management -- Imaging Scrotal Trauma -- Acute Scrotal Pain. Clinical features -- Acute Scrotal Pain. Management -- Imaging Acute Scrotal Pain in Adults 1.Torsion of the Testis and Appendages -- 2.Inflammation and other Disorders -- Imaging Acute Scrotal Pain in Children -- Painless Scrotal Lumps: Classification and Clinics -- Painless Scrotal Lumps: Current Therapeutic Approach and follow-up -- Imaging Scrotal Lumps in Adults 1.Tumors -- 2.Cysts and fluid Collections -- Imaging Scrotal Lumps in Children -- The Infertile Men 1.Clinical features -- 2.Sperm Analysis -- 3.Endocrinological Evaluation -- 4.Management of Obstructive Azoospermia -- 5.Management of Non-Obstructive Azoospermia -- Imaging the Infertile Men 1.Varicocele -- 2.Obstructive Syndromes and other Disorders -- The Undescended Testis. Prevalence and Clinical Features -- The Undescended Testis. Management: Microsurgery and Laparoscopy -- Imaging the Undescended Testis -- Incidental Scrotal Findings at Imaging 1.Calcifications -- 2.Miscellaneous Benign Conditions -- Nuclear Medicine Methods in Scrotal Imaging -- Contrast Enhanced US of the Scrotum.
Keywords: Radiology; Urology; Gynecology .; Imaging / Radiology; Diagnostic Radiology; Urology; Gynecology